The PON “Reti e mobilità” and the objectives of Sustainability: the role of the Environmental Monitoring Plan. - Bella, Francesco; Ferrara, Floriana Federica; Perricone, Roberto Salvatore; Poleggi, Giovanni; Antonini, Maria Rita; Baratono, Pietro (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The National Operative Program (PON) “Reti e mobilità” has been approved by European Commission on the 7th of December 2007. The strategic approach of the PON, exclusively devoted to the so-called “convergence regions” of Italy (Campania, Calabria, Sicilia, Puglia), aims to: 1. improve the modal balance by an economic, social and environmental perspective; 2. develop the inter-modality in order to move towards the integration of convergence area into the network of the European transport system; 3. improve the mobility and the accessibility, also to reduce the traffic congestion; 4. increase the efficiency related to security standards, to management techniques and to the quality of transportation services in the sector of freight; 5. guarantee the reduction of environmental impacts through a global improvement of the efficiency of the transport systems. In such a way it is clear that the PON “Reti e mobilità” takes greatly into account the Sustainability principles recognized at European scale as attested by the budget, namely over the 70% of the entire fund, associated with low-impacts infrastructures (railways and harbors). The PON has been submitted to the SEA procedure, following what the 2001/42/CE Directive establishes. The Environmental Report of PON devotes great attention to the monitoring activity as shown by the reported recommendation about the need for adequate measures for the environmental monitoring, also in order to apply corrective measures during the implementation of the program. By this point of view, a first and important step has been the elaboration of the “Environmental Monitoring Plan” (EMP) that represents the main methodological document for the following implementation of the monitoring activity. This paper, after a brief presentation of the program and of the objectives of Sustainability that the Programs aims to pursue through the realization of specific projects, is devoted to introduce the Environmental Monitoring Plan of the PON that has been approved by the Ministry of the Infrastructures and Transport -in charge as Management Authority of the PON- in February 2011. In detail, the PMA represents the tool through which, the Management Authority, that has specific responsibilities and functions in terms of monitoring and environmental assessment of the program, controls the significant impacts on the environment caused by the implementation of the PON and verify the level of achievement of the established objectives of environmental sustainability. The structure of EMP is based on three main aspects: 1) the adoption of the results of other interesting experiences carried out by experts institutions on the topic; 2) an approach favoring the creation of an “integrated” monitoring system with the others Operative Programs activated at regional scale; 3) the implementation of a cooperation and shared process with all the directly-involved actors.